Analisis Event Budaya Sapi Sono dan Karapan Sapi Piala Presiden 2024 Guna Membangun Brand Awareness dan Brand Image Wismilak Diplomat di Madura - Tania Nanda Pangestu; Survival Survival; Wahju Wulandari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research analyzes the effectiveness of Wismilak Diplomat's sponsorship of the 2024 Presidential Cup Sapi Sono and Karapan Sapi cultural events as a marketing strategy to increase brand awareness and brand image in Madura. Using qualitative methods with a case study approach, this research examines the impact of sponsorship on audience engagement and brand perception through branding elements, interactive activities and digital media. The research results show that culture-based sponsorship has a positive impact on brand awareness and image, especially through direct interaction with the audience and broad media exposure. However, there are challenges in optimizing digital media and the effectiveness of branding elements at event locations. Therefore, more adaptive and innovative sponsorship strategies are needed to increase the impact of culture-based marketing in the future.